Evaluation of semen quality of buffalo frozen semen produced by Artificial Insemination Center - Mahendra, H. C.; Samsudewa, D.; Ondho, Y. S. (Journal of the Indonesian Tropical Animal Agriculture, 2018)
This study aimed to evaluate and compare the quality of post thawing spermatozoa of buffalo frozen semen produced by artificial insemination centers on standard values, and proposed reference values (PRV). Materials of the research were 60 samples of straws obtained from three Artificial Insemination Center, which are each 20 straws, respectively. Parameters observed were motility, concentration, longevity, plasma membrane integrity (PMI), acrosome integrity (AIn) and recovery rate. The obtained data were tested by Z test then presented as mean ± standard deviation. The research results from three artificial insemination center showed that motility mean was 45.00±3.07%, concentration mean was 26.09±3.11 x106 cells/0.25mL, longevity mean was 10.38±0.75%/hour, PMI mean was 45.86±10.67%, AI mean was 73.99±5.28% and recovery rate mean was 64.38±5.16%. The conclusions of this research were the motility and concentration mean were higher than Indonesian National Standard (INS), longevity mean was lower than Department of Animal Husbandry, Dairying and Fisheries (DADF) standard but PMI and AIn mean were higher, the mean value of recovery rate was higher than of proposal value.